The role of clinical reminder system to drug prescribing on patients of the National Health Insurance with ischemic stroke - Faramita Hiola; Iwan Dwiprahasto; Rizaldy Pinzon (Universitas Gadjah Mada, 2022)
Since 2014 Indonesia has entered the era of universal health coverage (UHC) and public health financing system managed by the Social Security Organizing Agency Law/SSOAL (Badan Penyelenggara Jaminan Sosial/BPJS) . In this system, a national formulary was used as the basis for prescribing drugs by clinicians. One effort for quality and cost control in UHC was to develop a clinical reminder system (CRS) to help prescriber set treatment options in accordance with the national formulary. The aim of this study was to measure the role of CRS to the compatibility of drug prescribing in patients with ischemic stroke in Bethesda Hospital Yogyakarta, Indonesia. This study was carried out using quasi-experimental with pre-test and post-test design. The subjects of this study were outpatient ischemic stroke and the National Health Insurance (NHI) participant, age >18 years and had complete medication data. Prescribing data were compared between stroke patients treated at the hospital before and after implementation of CRS. The study was performed in 200 National Health Insurance (NHI) scheme outpatients with ischemic stroke. The groups consisted of 100 patients without CRS and 100 patients with CRS. The basic characteristics of both groups were similar. The results showed that after implementation of CRS, a significant improvement in the compliance of the neurologist prescribing medicine used to be available only in national formulary (RR: 1.02; 95% CI=1.00-1.04; p=0.015). Among others the most significant improvement was the prescription of antidyslipidemic using HMG-CoA medicine available in formulary. In conclusion, CRS can improve the compliance of prescribing with national formulary in stroke ischemic patients.